Inheritance of the reduced mitochondria of Giardia intestinalis is coupled to the flagellar maturation cycle - Tůmová, Pavla; Voleman, Luboš; Klingl, Andreas; Nohýnková, Eva; Wanner, Gerhard; Doležal, Pavel (BMC biology, 2021)
BACKGROUND: The presence of mitochondria is a distinguishing feature between prokaryotic and eukaryotic cells. It is currently accepted that the evolutionary origin of mitochondria coincided with the formation of eukaryotes and from that point control of mitochondrial inheritance was required. Yet, the way the mitochondrial presence has been maintained throughout the eukaryotic cell cycle remains a matter of study. Eukaryotes control mitochondrial inheritance mainly due to the presence of the genetic component; still only little is known about the segregation of mitochondria to daughter cells during cell division. Additionally, anaerobic eukaryotic microbes evolved a variety of genomeless mitochondria-related organelles (MROs), which could be theoretically assembled de novo, providing a distinct mechanistic basis for maintenance of stable mitochondrial numbers. Here, we approach this problem by studying the structure and inheritance of the protist Giardia intestinalis MROs known as mitosomes. RESULTS: We combined 2D stimulated emission depletion (STED) microscopy and focused ion beam scanning electron microscopy (FIB/SEM) to show that mitosomes exhibit internal segmentation and conserved asymmetric structure. From a total of about forty mitosomes, a small, privileged population is harnessed to the flagellar apparatus, and their life cycle is coordinated with the maturation cycle of G. intestinalis flagella. The orchestration of mitosomal inheritance with the flagellar maturation cycle is mediated by a microtubular connecting fiber, which physically links the privileged mitosomes to both axonemes of the oldest flagella pair and guarantees faithful segregation of the mitosomes into the daughter cells. CONCLUSION: Inheritance of privileged Giardia mitosomes is coupled to the flagellar maturation cycle. We propose that the flagellar system controls segregation of mitochondrial organelles also in other members of this supergroup (Metamonada) of eukaryotes and perhaps reflects the original strategy of early eukaryotic cells to maintain this key organelle before mitochondrial fusion-fission dynamics cycle as observed in Metazoa was established.
Keywords: organely; Mitochondrial Dynamics; mitochondrial evolution; Mitochondria; databáze genetické; Cytoskeleton; Databases, Genetic; Organelles; Mitochondrial inheritance; Mitosomes; Flagellum; Mitochondrial division; Protist; mitochondrie; Giardia; Giardia lamblia; mitochondriální dynamika; Cell cycle